Reducing wandering by persons with dementia using differential reinforcement. - Heard, K (1999)
Wandering behavior of 4 geriatric patients with dementia residing in a long-term care facility was assessed using direct behavioral observations. The consequences identified during the observations as maintaining wandering for each patient were then applied for the absence of wandering using differential reinforcement of other behavior (DRO). The effectiveness of the DRO procedure was evaluated using an ABAB design. Results indicated significant reductions in wandering during treatment.